Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) $\frac{{14}}{{18}}:\frac{8}{9} = \frac{7}{9}:\frac{8}{9} = \frac{7}{9} \times \frac{9}{8} = \frac{{63}}{{72}} = \frac{7}{8}$
b) $\frac{9}{6}:\frac{3}{{10}} = \frac{3}{2}:\frac{3}{{10}} = \frac{3}{2} \times \frac{{10}}{3} = \frac{{30}}{6} = 5$
c) $\frac{4}{5}:\frac{{10}}{{15}} = \frac{4}{5}:\frac{2}{3} = \frac{4}{5} \times \frac{3}{2} = \frac{{12}}{{10}} = \frac{6}{5}$
d) $\frac{1}{6}:\frac{{21}}{9} = \frac{1}{6}:\frac{7}{3} = \frac{1}{6} \times \frac{3}{7} = \frac{3}{{42}} = \frac{1}{{14}}$
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1-\left(\frac{12}{5}+y=\frac{8}{9}\right):\frac{16}{9}=0\)
\(1-\left(\frac{12}{5}+y-\frac{8}{9}\right)=0\times\frac{16}{9}\)
\(1-\left(\frac{12}{5}+y-\frac{8}{9}\right)=0\)
\(\frac{12}{5}+y-\frac{8}{9}=1-0\)
\(\frac{12}{5}-y+\frac{8}{9}=1\)
\(\frac{12}{5}-y=1-\frac{8}{9}\)
\(\frac{12}{5}-y=\frac{1}{9}\)
\(y=\frac{12}{5}-\frac{1}{9}\)
\(y=\frac{108}{45}-\frac{5}{45}\)
\(y=\frac{103}{45}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a.\frac{4}{3}-\frac{3}{2}:X=\frac{1}{6}\)
\(\frac{3}{2}:X=\frac{4}{3}-\frac{1}{6}\)
\(\frac{3}{2}:X=\frac{8}{6}-\frac{1}{6}\)
\(\frac{3}{2}:X=\frac{7}{6}\)
\(X=\frac{3}{2}:\frac{7}{6}\)
\(X=\frac{3}{2}\times\frac{6}{7}\)
\(X=\frac{9}{7}\)
\(b.\left(X+\frac{2}{3}\right):\frac{1}{3}=\frac{41}{3}\)
\(X-\frac{2}{3}=\frac{41}{3}.\frac{1}{3}\)
\(X-\frac{2}{3}=\frac{41}{9}\)
\(X=\frac{41}{9}+\frac{2}{3}\)
\(X=\frac{41}{9}+\frac{6}{9}\)
\(X=\frac{47}{9}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{3}{7}+\frac{4}{5}+\frac{4}{7}=\left(\frac{3}{7}+\frac{4}{7}\right)+\frac{4}{5}=1+\frac{4}{5}=\frac{9}{5}\)
\(\frac{6}{11}+\frac{1}{3}+\frac{5}{11}=\left(\frac{6}{11}+\frac{5}{11}\right)+\frac{1}{3}=1+\frac{1}{3}=\frac{4}{3}\)
a) \(\frac{3}{7}+\frac{4}{5}+\frac{4}{7}\)
= \(\left(\frac{3}{7}+\frac{4}{7}\right)+\frac{4}{5}\)
= \(1+\frac{4}{5}\)
= \(\frac{9}{5}\)
b) \(\frac{6}{11}+\frac{1}{3}+\frac{5}{11}\)
= \(\left(\frac{6}{11}+\frac{5}{11}\right)+\frac{1}{3}\)
= \(1+\frac{1}{3}\)
= \(\frac{4}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
M = (345 x (6789 + 3456 - 245)/690) x 99/100 x 98/99 x...x 2/3 x 1/2
M = ((345 x 10000)/690) x 99/2 (rút gọn)
M = (10000/2) x 99/2
M = 5000 x 99/2
M = 247500
Ok nha
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1.a,\frac{5}{7}=\frac{5.9}{7.9}=\frac{45}{63};\frac{4}{9}=\frac{4.7}{9.7}=\frac{28}{63}.\)
\(b,\frac{7}{15},\frac{5}{3}=\frac{5.5}{3.5}=\frac{25}{15}\)
\(c,\frac{11}{12}=\frac{11.4}{12.4}=\frac{44}{48};\frac{7}{48}\)
\(d,\frac{3}{2}=\frac{3.3}{2.3}=\frac{9}{6};\frac{2}{3}=\frac{2.2}{3.2}=\frac{4}{6}\)
\(e,\frac{1}{3}=\frac{1.4}{3.4}=\frac{4}{12};\frac{5}{4}=\frac{5.3}{4.3}=\frac{15}{12};\frac{10}{12}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x+\frac{2}{3}=\frac{9}{11}\)
\(x=\frac{9}{11}-\frac{2}{3}\)
\(x=\frac{5}{33}\)
\(x-\frac{3}{10}=\frac{4}{15}\)
\(x=\frac{3}{10}-\frac{4}{15}\)
\(x=\frac{1}{10}\)
\(x\times\frac{1}{7}=\frac{5}{6}\)
\(x=\frac{5}{6}:\frac{1}{7}\)
\(x=\frac{35}{6}\)
\(x:\frac{3}{5}=\frac{1}{6}\)
\(x=\frac{3}{5}.\frac{1}{6}\)
\(x=\frac{1}{10}\)
+, \(x+\frac{2}{3}=\frac{9}{11}\)
\(x=\frac{9}{11}-\frac{2}{3}=\frac{5}{33}\)
+, \(x-\frac{3}{10}=\frac{4}{15}\)
\(x=\frac{4}{15}+\frac{3}{10}=\frac{17}{30}\)
+, \(x\cdot\frac{1}{7}=\frac{5}{6}\)
\(x=\frac{5}{6}:\frac{1}{7}=\frac{5}{6}.\frac{7}{1}=\frac{35}{6}\)
+,\(x:\frac{3}{5}=\frac{1}{6}\)
\(x=\frac{1}{6}\cdot\frac{3}{5}=\frac{3}{30}=\frac{1}{10}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\left(\frac{6}{11}+\frac{5}{11}\right)\times\frac{3}{7}\)
Cách 1: \(\left(\frac{6}{11}+\frac{5}{11}\right)\times\frac{3}{7}=1\times\frac{3}{7}=\frac{10}{7}\)
Cách 2: \(\left(\frac{6}{11}+\frac{5}{11}\right)\times\frac{3}{7}=\frac{6}{11}\times\frac{3}{7}+\frac{5}{11}\times\frac{3}{7}=\frac{18}{77}+\frac{15}{77}=\frac{33}{77}=\frac{3}{7}\)
\(b,\frac{3}{5}\times\frac{7}{9}+\frac{3}{5}\times\frac{2}{9}\)
Cách 1: \(\frac{3}{5}\times\frac{7}{9}+\frac{3}{5}\times\frac{2}{9}=\frac{7}{15}+\frac{2}{15}=\frac{9}{15}\)
Cách 2: \(\frac{3}{5}\times\frac{7}{9}+\frac{3}{5}\times\frac{2}{9}=\frac{3}{5}\times1=\frac{3}{5}\)
P/s: Ý B có vấn đề thì phải
\(a,\left(\frac{6}{11}+\frac{5}{11}\right)x\frac{3}{7}\)
\(=\frac{11}{11}=1x\frac{3}{7}\)
\(=\frac{3}{7}\)
cach 2
\(\frac{6}{11}x\frac{3}{7}+\frac{5}{11}x\frac{3}{7}\)
\(=\frac{18}{77}+\frac{15}{77}\)
\(=\frac{33}{77}=\frac{3}{7}\)
\(b,\frac{3}{5}x\frac{7}{9}+\frac{3}{5}x\frac{2}{9}\)
\(=\frac{21}{45}+\frac{6}{45}\)
\(=\frac{27}{45}=\frac{3}{5}\)
cách 2 :
\(\frac{3}{5}x\left(\frac{7}{9}+\frac{2}{9}\right)\)
\(=\frac{3}{5}x\frac{9}{9}\)
\(=\frac{27}{45}=\frac{3}{5}\)
\(\dfrac{5}{11}-\left(\dfrac{3}{5}-\dfrac{6}{11}\right)\)
\(=\dfrac{5}{11}-\dfrac{3}{5}+\dfrac{6}{11}\)
\(=\left(\dfrac{5}{11}+\dfrac{6}{11}\right)-\dfrac{3}{5}\)
\(=1-\dfrac{3}{5}\)
\(=\dfrac{5}{5}-\dfrac{3}{5}\)
\(=\dfrac{2}{5}\)
`5/11-(3/5-6/11)`
`=5/11-3/5+6/11`
`=(5/11+6/11)-3/5`
`=1-3/5`
`=2/5`